(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rosa E, Ekowati CN, Handayani TT, Ikhsanudin A, Apriliani F, Arifiyanto A. 2020. Characterization of entomopathogenic fungi as a natural biological control of American cockroaches (Periplaneta americana). Biodiversitas 21: 5276-5282. Eradicating cockroaches using chemical insecticides produces residues that contaminate the environment and promote insect resistance. Biological control has become an option for controlling cockroaches. The use of entomopathogenic fungi is one of them. The aim of this study was to obtain a fungal isolate that was effective at killing cockroaches. The result of entomopathogenic fungi isolation from cockroaches obtained 4 isolates, IK1, IK2, IK3 isolates were included in the Aspergillus genus while IK4 was Penicillium. Extracellular enzymes serve as screening materials for biocontrol candidates. IK1 and IK3 isolates showed higher chitinase activity than the other two isolates. The highest mortality of Periplaneta americana at nymphs stage was 60% achieved by the treatment of Aspergillus sp. IK3 with a concentration of 109 conidia/ mL. In adult stage cockroach the mortality was increased to 86%.